Bergamottin and Its Role as Inhibitors of CYP3A4 - จักรทอง สุดา (KKU Science Journal, 2012)
Bergamottin, is a furanocoumarin compound, isolated as a major component from grapefruit juice which has been found to inhibit cytochrome P450 (CYP) 3A4, leading to the possibility of a patient overdose. Coadministration of grapefruit juice with drugs including calcium channel blockers, immonosuppressants, antihistamines and cholesterol-lowing statins resulted in substantial increases in their oral bioavailabilities, which are in some cases accompanied by the alteration of drug and drug toxicity. An alkyl substituent at the 5-position on the furanocoumarin is essential for the interaction with CYP3A4. The inhibitory potency of the furanocoumarin was enhanced by the incorporation of geranyloxy derived moieties with hydrophilic groups at the 6’, 7’-position.